2012
DOI: 10.1002/jrs.3171
|View full text |Cite
|
Sign up to set email alerts
|

CARS and SHG microscopy to follow collagen production in living human corneal fibroblasts and mesenchymal stem cells in fibrin hydrogel 3D cultures

Abstract: Coherent anti-Stokes Raman scattering (CARS) microscopy is combined with second harmonic generation (SHG) technique in order to follow the early stage of stem cell differentiation within a 3D scaffold.One of the first evidence of hMSCs differentiation is the formation of an extracellular matrix (ECM) where the collagen protein is its main component.This work demonstrated the multimodal CARS and SHG microscopy as a powerful non-invasive label free technique to follow the collagen production in living cell 3D cu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 48 publications
0
24
0
Order By: Relevance
“…Employing the multimodal CARS/TPEF microscope realized as described in a previous paper [36], the PLGA/gelatin scaffold was 3D imaged simultaneously with the hMSCs using CARS and TPEF techniques, respectively. CARS signal was measured in forward detection, in a spectral range between 716 nm and 770 nm, while TPEF signal in epidetection in a spectral range between 510 nm and 570 nm.…”
Section: Methodsmentioning
confidence: 99%
“…Employing the multimodal CARS/TPEF microscope realized as described in a previous paper [36], the PLGA/gelatin scaffold was 3D imaged simultaneously with the hMSCs using CARS and TPEF techniques, respectively. CARS signal was measured in forward detection, in a spectral range between 716 nm and 770 nm, while TPEF signal in epidetection in a spectral range between 510 nm and 570 nm.…”
Section: Methodsmentioning
confidence: 99%
“…Mortati, Divieto, and Sassi applied CARS and second‐harmonic generation microscopy to follow collagen production in living human corneal fibroblasts and mesenchymal stem cells in fibrin hydrogel 3‐D cultures. Their findings indicate that multimodal CARS and second‐harmonic generation imaging can be used as a new way of monitoring the differentiation of stem cells by evaluating the production of collagen in both short and long‐term experiments . Shapiro, Konorov, and Milner described interference spectroscopy associated with CARS from noisy broadband pulses.…”
Section: Nonlinear and Related Time‐resolved Raman Spectroscopymentioning
confidence: 99%
“…In our previous work (Marabello et al, 2015), we reported a theoretical and experimental study on the NLO properties of two MOFs obtained from fructose and calcium chloride, [Ca(C 6 H 12 O 6 ) 2 (H 2 O) 2 ]Cl 2 ÁH 2 O (CaFruCl) and [Ca(C 6 H 12 O 6 )-(H 2 O) 2 ]Cl 2 (CaFruCl-2). We measured (Mortati et al, 2012) their SH intensity by SHG microscopy and showed that the coordination of fructose on the calcium ion improves the SH efficiency with respect to fructose itself, probably by both the induced lowering of symmetry and the dissociation of CaCl 2 . In this work we extended our investigation on MOFs obtained from fructose and other alkali-earth halogenides to better understand the effect of the size of the cation and the different polarizability of the anion in isomorphic structures on the calculated hyperpolarizability and optical susceptibility, which in turn are related to the SHG efficiency.…”
Section: Introductionmentioning
confidence: 97%